Bypassing clinical research for secondary evidence synthesis: are systematic reviews replacing clinical research for medical students and residents in Pakistan? - Farooq Azam Rathore; Farooq, Fareeha; Wajid, Gohar (Journal of the Pakistan Medical Association, 2026)
In recent years, there has been a significant increase in the number of systematic reviews and meta-analyses authored by medical students, residents and novice researchers in Pakistan. Although developing skills in evidence synthesis is valuable, this trend has an unforeseen consequence: many of these reviews are conducted without the necessary clinical experience or subject matter expertise. These publications often are on diseases, diagnostic methods and treatments that are rarely encountered. This raises concerns about the purpose, relevance and educational value of such work. A balanced approach is recommended between conducting clinical research and relevant systematic reviews and meta-analyses. While the importance of systematic reviews and meta-analyses is duly recognised, students and residents must be encouraged to also engage in studies directly relevant to local clinical issues. Such a point of view is not a critique, but an effort to reshape the current research culture that is driven by the “publish or perish” mentality. Research should be multi-dimensional, diverse, with an aim to encourage deeper learning, and a meaningful contribution to local healthcare needs. This cannot be achieved by bypassing foundational clinical research experience. Key Words: Systematic reviews, Research training, Pakistan, Evidence-based medicine, Clinical research, Research ethics, Medical students.